Evidences on alterations in skeleton composition and mineralization in a site-attached fish under naturally acidified conditions in a shallow CO2 vent - Mirasole, Alice; Scopelliti, Giovanna; Tramati, Cecilia; Signa, Geraldina; Mazzola, Antonio; Vizzini, Salvatrice (Science of The Total Environment, 2021)
Background: Ocean acidification may affect fish mineralized structures (i.e. otoliths and skeleton). Methods: Here,we compared the elemental composition of muscle and skeleton and themineral features of skeleton in the site-attached fish Gobius bucchichi naturally exposed to high pCO2/lowpH conditions in a shallow CO2 vent with fish of the same species exposed to normal pH. Results: Overall, no skeleton malformations were found in both pH conditions, but among-site differences were found in the elemental composition. Interestingly, higher Ca/P values, inducing a moderate skeleton maturation, were found in fish exposed to acidified conditions than in controls. Conclusion: Our findings suggest that ocean acidification may play a significant role in physiological processes related to mineralization, fostering skeleton pre-aging.